Relationships Between Performance and Injury Occurrence in Athletics (Track and Field): A Pilot Study on 8 National-Level Athletes From Sprints, Jumps and Combined Events Followed During at Least Five Consecutive Seasons - Chapon, Joris; Navarro, Laurent; Edouard, Pascal (Frontiers in Sports and Active Living, 2022)
Objective: To analyse the potential association between performance and occurrence of injuries in national-level athletics athletes from sprints, jumps and combined events through several seasons. Methods: We performed a retrospective analysis of performance and injury data collected prospectively in 8 national-level athletics athletes followed during at least five consecutive seasons from 2009 to 2019. For each athlete, we performed a descriptive analysis of the performances and injuries, and we performed four several binomial logistic regressions with 1) national championships participation (yes/no) or 2) international competition participation (yes/no) as dependent variable, and all injury (yes/no) or TLI (yes/no) as independent variables, adjusted for individual athlete and number of season, and for national championships participation (yes/no) for international competition participation outcome with Odd Ratios (OR) with 95% confidence intervals (95%CI). Results:There was an average of 2.7±1.7 “all-injuries” and 0.9±0.6 TLI per athlete per season over the study period. The occurrence of all injuries was significantly associated with higher odds of national championships participation (OR=4.85 [95% CI 3.10 to 3050.5], p=0.021). The occurrence of TLI was significantly associated with higher odds of national championships participation (OR=133.6 [95% CI 4.92 to 14251.5], p=0.013). The occurrence of all injuries or TLI were associated with insignificant lower odds of international championships participation. Conclusions: Despite the caution that should be taken in the interpretation of our results, our present study confirms the interest and relevance of injury risk reduction approach in athletics.